Trabalho autônomo e conflitos: o comércio ambulante no território dos trens - Silva, José Carlos Brito (2009)
This research analyzes and seeks to understand the increase in informal activities in general and mobile commerce as a particular case and the conflict between the public and employees of these itinerant trade. This analysis is performed as a result of the dynamics inherent in the capitalist system that is based on socioeconomic contradictions, among them the need to generate a surplus of labor to thus have its disposal an army reserve. In that sense this analysis takes into account the urbanization process as RMSP suffered by one of the promotion of unemployment which had their causes in several variables. The phenomenon of the increase in practice of these activities, named in this study as "independent work", practiced by itinerant workers in trains and other public spaces of RMSP, has widened from the 80's resulting from economic crises that hit the country causing huge recession unemployment and an economy that can be described as the results of politics applied at that moment. This unemployment is particularly accentuated in the 90s resulting from the economic opening process undertaken by the Brazilian Government as a way of integrating the country in the process of globalization. The way this integration, was made, marked by unbridled economic openness, reflected in several aspects of the economy of the country: it has a new territoriality of plants provided by the development of technical-scientific-media informational affectry RMSP mainly because this the most industrialized in the country, it also involves a process of productive restructuring in which the industrial sector loses its economic space and it is substituted by tertiary activities; as a consequence implemented a new model of administrative organization and the production process adopted by enterprises, the model flexible also called post-fordist, requiring a new profile with more and better professional qualifications to perform the tasks, now with a greater degree of complexity and flexibility. These changes reflected directly in the levels of unemployment now reaching ever higher rates. Informal activities in general and labor have become mobile, thus a way to ensure survival for the huge number of unemployed, to consolidate is not as alternatives but rather as a temporary work, by effective work. Just as the growing number of than practitioners in itinerant trade grew the conflicts that came to rely even violently with police actions undertaken. The territory of the CPTM trains as public spaces and great appeal to the trade due to the large flow of passengers, has become one of those places where this picture was reflected socioeconomic and conflict is fierce. This territory, which offers easier to enable practitioners of this activity a condition of legalization of the organization and activities to provide decent conditions for a significant number of workers was the locus chosen in this research as part of the complex and contradictory dynamics of capitalist economy